Evolution of Kenya’s Foreign Policy During the Cold War - Danvas Mabeya (African Journal of Political Science)
This study critically outlines Kenya’s Foreign Policy as it evolved during the cold war under Moi’s era toward the Middle East. The study exemplifies the underlying strategies, sources, national and personal interests, objectives, priorities, and implementation of Kenya's foreign policy. The study is premised on the need to elucidate if Kenya’s belief in regional peace and security was the cornerstone under which Kenya’s foreign was formulated and implemented. It was believed that any inconsistencies in Kenya’s foreign policy were based on rational and emerging trends in international affairs such as security threats to regional and global peace and stability. The study aims to ascertain how, Kenya’s recognition policy, was formulated, articulated, and exercised during Moi’s era toward the Middle East (1978-1990). The central question of this study is this: What influenced Kenya’s recognition policy towards Afghanistan, Iraq, Iran, Israel, and Palestine during the Cold War under Moi’s administration (1978-1990)?